Avaliação biomecânica de diferentes métodos de osteossíntese após osteotomia sagital mandibular em grandes avanços - Klein, Gustavo Batista Grolli (2016)
The aim of this study was to assess the biomechanical stability of 6 different osteosynthesis, after sagittal split osteotomy. Sixty polyurethane hemi-mandibles were assigned to 2 groups, containing 6 subgroups each. After 10-mm advancement of the distal segment (group1) and 10-mm advancement combined with 20° counterclockwise rotation (group2), the bone segments were fixed by different osteosynthesis methods using 2.0-mm plates/screws: Subgroup A, one conventional straight plate; Subgroup B, two conventional straight plates; Subgroup C, one conventional sagittal plate; Subgroup D, one locking straight plate; Subgroup E, two locking straight plates; Subgroup F, one locking sagittal plate. The hemi-mandibles were loaded in compressive strength, by a 3-point biomechanical test, until 3-mm displacement occurred between segments. In all cases, the fixations showed better performance in group 1 than group 2, with statistical significance in subdivisions A, C, and D (p<0,05). The use of 2 straight mini-plates showed more resistance, followed by sagittal mini-plates in both groups. However, in counterclockwise rotations, the use of two conventional straight plates showed no statistical significance against sagittal locking plate (p<0,05). This study shows that two plates is the form of fixation with less displacement. If the clinician opts to use one plate, sagittal plate is the best alternative